Ab-initio calculations on static and dynamic third-order optical nonlinearity of azo-azulenes - Karakas, A.; El kouari, Y.; Migalska- Zalas, A.; Sahraoui, B. (Photonics Letters of Poland, 2012)
To provide an insight into the microscopic third-order nonlinear optical (NLO) behavior of a series of azo-azulenes; both dispersion-free (static) and also frequency-dependent (dynamic) linear polarizabilities (alpha) and second hyperpolarizabilities (gamma) at 532 nm wavelength have been theoretically investigated by means of time-dependent Hartree-Fock (TDHF) method. The maximum one-photon absorption (OPA) wavelengths recorded by quantum mechanical computations using a configuration interaction (CI) method are estimated in the visible region, supporting the pi->pi* transitions. The ab-initio calculation results with non-zero values on (hyper)polarizabilities indicate that the title compounds might possess microscopic third-order NLO phenomena. Full Text: PDF References D.M. Burland, R.D. Miller, C.A. Walsh, "Second-order nonlinearity in poled-polymer systems", Chem. Rev. 94, 31 (1994)[CrossRef] T.G. Pedersen, K. Pedersen, P. K. Kristensen, J. Rafaelsen, N. Skivesen, Z. Li, S. V. Hoffmann, "Theoretical and experimental studies of photoemission from Al quantum wells on Si(111)", Surf. Sci. 516, 127 (2002)[CrossRef] A. Karakaş, Z. Erdem Koç, M. Fridrichová, P. Němec, J. Kroupa, "The investigation of second-order nonlinear optical properties of p-nitrophenylazoaniline: second harmonic generation and ab initio computations", J. Theoretical and Computational Chemistry 11, 209 (2012)[CrossRef] D.R. Kanis, M.A. Ratner, T. Marks, "Design and construction of molecular assemblies with large second-order optical nonlinearities. Quantum chemical aspects", Chem. Rev. 94, 195 (1994)[CrossRef] A. Elmali, A. Karakaş, H. Ünver, "Nonlinear optical properties of bis[(p-bromophenyl-salicylaldiminato)chloro]iron(III) and its ligand N-(4-bromo)-salicylaldimine", Chem. Phys. 309, 251 (2005)[CrossRef] Z. Essaidi, J. Nizioł, B. Sahraoui, "Azo-azulene based compounds-nonlinear optical and photorefractive properties", Opt. Materials 33(9), 1387 (2011)[CrossRef] R.J. Bartlett, H. Sekino, G.D. Purvis, "Comparison of MBPT and coupled-cluster methods with full CI. Importance of triplet excitation and infinite summations", Chem. Phys. Lett. 98, 66 (1983)[CrossRef] I.M. Kenawi, A.H. Kamel, R.H. Hilal, "BSSE effects on the static dipole polarizability and first dipole hyperpolarizability of diclofenac sodium", J. Mol. Struct. 851, 46 (2008)[CrossRef] C.E. Dykstra, "Dipole (electric field) and quadrupole (field gradient) polarizabilities of hydrogen, nitrogen, and acetylene from the application of derivative Hartree–Fock theory", J. Chem. Phys. 82, 4120 (1985)[CrossRef] G. Maroulis, "On the accurate theoretical determination of the static hyperpolarizability of trans-butadiene", J. Chem. Phys. 111, 583 (1999)[CrossRef] Intel86 (win32, Linux, OS/2, DOS) version. PC GAMESS version 6.2, build number 2068; described in: M. W. Schmidt et. al., "General atomic and molecular electronic structure system", J. Comput. Chem. 14, 1347 (1993)[CrossRef] M.P. Bogaard, B. Orr, Ed.: A.D. Buckingham, MTP International review of science, vol. 2 (Butterworths, London 1975). M.J. Frisch et al., Gaussian 03, Revision E.01 (Gaussian, Inc., Wallingford CT 2004). Y.R. Shen, Proc. Natl. Acad. Sci. U.S.A. 93, 112104 (1996). J. Kulakowska, S. Kucharski, "New chromophoric monomers with nonlinear optical properties", Eur. Polym. J. 36, 1805 (2000)[CrossRef] I.D.L. Albert, T.J. Marks, M. A. Ratner, "Large Molecular Hyperpolarizabilities in “Push-Pull” Porphyrins. Molecular Planarity and Auxiliary Donor-Acceptor Effects", Chem. Mater. 10, 753 (1998)[CrossRef] S. Di Bella, I. Fragala, I. Ledoux, M.A. Diaz-Garcia, P.G. Lacroix, T.J. Marks, "Sizable Second-Order Nonlinear Optical Response of Donor-Acceptor Bis(salicylaldiminato)nickel(II) Schiff Base Complexes", Chem. Mater. 6, 881 (1994)[CrossRef] J.L. Brédas, C. Adant, P. Tackx, A. Persoons, "Third-Order Nonlinear Optical Response in Organic Materials: Theoretical and Experimental Aspects", Chem. Rev. 94, 243 (1994)[CrossRef] G. Maroulis, D. Xenides, U. Hohm, A. Loose, "Dipole, dipole–quadrupole, and dipole–octopole polarizability of adamantane, C10H16, from refractive index measurements, depolarized collision-induced light scattering, conventional ab initio and density functional theory calculations", J. Chem. Phys. 115, 7957 (2001)[CrossRef] G. Kelly, F. Darviche, N. Robertson, T. Gelbrich, M. B. Hursthouse, D.A. Thomas, I. R. Butler, "Directly-linked intramolecular donor–acceptor compounds of ferrocene and tetracyanoanthraquinodimethane", Inorganic Chem. Com. 8 (No. 10), 874 (2005)[CrossRef]